Effects of mindfulness practice on performance and factors related to performance in long-distance running: A systematic review - Corbally, L.; Wilkinson, M.; Fothergill, M. A. (Journal of Clinical Sport Psychology, 2020)
Fatigue, boredom, pain, performance anxiety, and negative thoughts are challenges characteristic of competitive running. One psychological technique that is gainingsupport and has been successfully implemented in sport is the practice of mindful-ness. Where conventional psychological skills training interventions aim to changedysfunctional thoughts and emotions, mindfulness focuses on altering the relation-ship to physiological and psychological states. This could help in dealing with thedemands of distance running but this has yet to be examined. This article was focusedon reviewing mindfulness interventions on performance and performance-basedfactors in long distance running, assessing (a) mindfulness scores, (b) physiologicalperformance-related factors, (c) psychological performance-related factors, and(d) performance outcomes. A search of relevant electronic databases yielded sevenstudies which met the inclusion criteria. The review provided some tentative supportfor the use of mindfulness interventionsregarding: reducing competitive anxiety,attenuating immune responses to high-intensity running, and increasing state mind-fulness. However, due to the methodological weaknesses of studies more research isrequired using high-quality randomized controlled trial designs.